Revising the definition of “demand satisfied for modern methods of family planning:” A cross-sectional study to explore incorporating person-centered constructs of demand, choice, and satisfaction - Jewel Gausman; Niranjan Saggurti; Richard Adanu; Delia A. B. Bandoh; Mabel Berrueta; Suchandrima Chakraborty; Ernest Kenu; Nizamuddin Khan; Ana Langer; Carolina Nigri; Magdalene A. Odikro; Veronica Pingray; et al. (PLoS ONE, 2025)
Several challenges to validity have been identified with standard approaches used to measure “demand satisfied for modern methods of family planning.” This study explored construct validity of the widely used indicator for “demand satisfied” by comparing the standard definition to alternative definitions of the indicator highlighting dimensions of women’s own perceived demand, choice, and satisfaction. This cross-sectional study of women aged 15–49 years was conducted in Argentina (n = 1492), Ghana (n = 1600), and India (n = 1702) using a two-staged random sampling design. Women were directly asked about their: 1) demand, whether they wanted to use a contraceptive method to prevent pregnancy; 2) choice, whether they had autonomy in decision-making during their last family planning visit; and 3) satisfaction, whether they were satisfied with their method. The values of the standard and alternative indicators were compared. Convergent validity was assessed using logistic regression to explore the association between indicator definition and use of a preferred contraceptive method. In Argentina and India, the percentage of women with demand satisfied after incorporating constructs of demand, choice, and satisfaction was substantially lower than that obtained using the standard definition—a reduction of ~70% in Argentina and ~40% in India. Women who were categorized as having their “demand satisfied” for family planning according to the person-centered dimensions of the alternative indicator were significantly more likely to be using their preferred method of contraception in all three countries (OR: 7.7, 95% CI: 5.31–11.07 in Argentina, OR: 4.83, 95% CI: 2.27–10.27 in Ghana, and OR: 2.07 95% CI: 1.11–3.86 in India) compared to those whose demand was satisfied by only the standard indicator definition. Revising the definition of demand satisfied to reflect the principles of person-centered care offers an opportunity to improve construct validity by ensuring that global measurement efforts align with women’s reproductive rights.